Interleukin-21: biology and application to cancer therapy - Andorsky, David J; Timmerman, John M (Expert opinion on biological therapy, 2008)
IL-21, a recently described common gamma-chain cytokine, can induce the maturation and enhanced cytotoxicity of natural killer (NK) and CD8(+) T cells and proliferation of CD40-stimulated B cells. Exogenous IL-21 has antitumor effects in murine models via immunological mechanisms. In addition, IL-21 can also directly induce apoptosis in chronic lymphocytic leukemia cells and other B cell lymphomas. We examine preclinical and clinical data regarding anticancer therapy with IL-21. Published original research, abstracts and ongoing clinical trials are reviewed. A brief summary of IL-21 biology is also provided. Three Phase I and II clinical trials with recombinant IL-21 have been completed, providing data on the safety and efficacy in subjects with advanced melanoma, renal cell carcinoma and non-Hodgkin's B cell lymphoma. Numerous additional single-agent and combination therapy clinical trials are ongoing for a variety of human malignancies. B cell malignancies in particular warrant further clinical investigation.